2016
DOI: 10.1016/j.juro.2016.06.081
|View full text |Cite
|
Sign up to set email alerts
|

Do Black NonHispanic Men Produce Less Prostate Specific Antigen in Benign Prostate Tissue or Cancer Compared to White NonHispanic Men with Gleason Score 6 (Grade Group 1) Prostate Cancer?

Abstract: Benign prostate tissue produces equal amounts of prostate specific antigen in black and white men. Gleason score 3+3=6 (Grade Group 1) prostate cancer produces less prostate specific antigen in black men. These data should be considered for lowering prostate specific antigen and its derivatives in determining biopsy thresholds and for adjusting values for active surveillance criteria in black men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Although PCa is the most commonly diagnosed non-cutaneous malignancy in Hispanic/Latino men [ 22 ], relatively little is known about low-risk disease in this population. Studies describing biological differences in tumor volume, location [ 5 ], PSA production [ 20 ], and performance of AS criteria [ 4 ] in NHB men provide useful information to enact meaningful changes in clinical screening and management of PCa. Despite recently reported inconsistencies in AS performance across NHW, NHB, and Hispanic/Latino men who underwent RP [ 4 , 5 , 10 ], AS criteria do not yet include race or ethnicity as variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although PCa is the most commonly diagnosed non-cutaneous malignancy in Hispanic/Latino men [ 22 ], relatively little is known about low-risk disease in this population. Studies describing biological differences in tumor volume, location [ 5 ], PSA production [ 20 ], and performance of AS criteria [ 4 ] in NHB men provide useful information to enact meaningful changes in clinical screening and management of PCa. Despite recently reported inconsistencies in AS performance across NHW, NHB, and Hispanic/Latino men who underwent RP [ 4 , 5 , 10 ], AS criteria do not yet include race or ethnicity as variables.…”
Section: Discussionmentioning
confidence: 99%
“…Variability in PSA production amongst racial/ethnic groups can be a result of biological or environmental factors. In recent findings, while accounting for TV, PW, and BMI, NHB men were shown to produce equal amounts of PSA from benign prostate tissue but 25% less from GS 3+3=6 (Grade Group 1) PCa compared to NHW men [ 20 ]. By further characterizing PSA-based tests in minority populations with homogenous, GS 3+3=6 (Grade Group 1) PCa, we can attempt to address risk stratification disparities by isolating and identifying contributing factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence also exists of unequal PSA amounts between white and African American men with prostate cancer . while some have postulated that benign prostate tissue in African Americans may contribute more PSA to the circulation than that of Whites, when prostate weight and PSA hemodilution because of different body weights are accounted for, benign prostate tissue produces equal amounts of PSA in African American and white men …”
Section: Introductionmentioning
confidence: 99%
“…Its low specificity and sensitivity are mainly attributable to the fact that serum PSA may also be increased in benign conditions, such as benign prostatic hyperplasia and chronic prostatitis. Additionally, serum PSA levels are affected by biologic variability that may be related to differences in androgen levels or prostate manipulation and may have distinct racial variation [ 6 ]. Ludwig et al recently reported that men with an undetectable serum PSA 20 years after radical prostatectomy had a very low rate of recurrence and no deaths due to prostate cancer, suggesting that 20 years is a reasonable time to discontinue PSA testing [ 7 ].…”
mentioning
confidence: 99%